2020
DOI: 10.1111/tct.13214
|View full text |Cite
|
Sign up to set email alerts
|

Improving medical students’ confidence in end‐of‐life consultations

Abstract: Background: End-of-life discussions are associated with improved quality of care for patients. In the UK, the General Medical Council outlines a requirement for medical graduates to involve patients and their families in discussions on their care at the end-of-life. However medical students feel ill-equipped to conduct these discussions. Methods: In 2018, Sheffield Medical School introduced a small group role-play session on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
(16 reference statements)
0
6
0
2
Order By: Relevance
“…Through routine administration of diverse, multimodal UME practices, recent literature supports that medical students may be able to enter residency with greater comfort and competency when conducting EOL conversations as trainees. [29][30][31] A 2023 study by Erlich et al 32 even suggested that writing one's own advance directive can be a helpful practice for medical students as they learn how to develop empathy, self-reflection, and intention with discussions of death and EOL care.…”
Section: Commentarymentioning
confidence: 99%
“…Through routine administration of diverse, multimodal UME practices, recent literature supports that medical students may be able to enter residency with greater comfort and competency when conducting EOL conversations as trainees. [29][30][31] A 2023 study by Erlich et al 32 even suggested that writing one's own advance directive can be a helpful practice for medical students as they learn how to develop empathy, self-reflection, and intention with discussions of death and EOL care.…”
Section: Commentarymentioning
confidence: 99%
“…Há um padrão dose-dependente na eficácia da atropina e na magnitude dos efeitos adversos. É necessária a realização de mais estudos com maiores grupos amostrais de pacientes em uso de atropina, em diferentes populações e por maior período de acompanhamento para realmente definir 83,84,86,87,88,89,90,91,92,281 Envelhecimento 42,43,44,45,47,49,50,51,172,281 Exame psíquico 238, 239 F Fisioterapia pediátrica 148,149,150,154,156 G 127,130,131,134,135 H Hérnia 28,29,30,31,200,201,202,203,204 Hernioplastia 27,28,29,30,31,32,199,200,202,204 Hospitais estratégicos 168,169 Humanização 83,84,87,88,89,90,91,…”
Section: Eduardo Figueiredo Beustunclassified
“…O uso de simulação parece promissor na formação médica, pois pode fazer com que os alunos se sintam menos desconfortáveis, inquietos ou desamparados ao pensar em cuidar de pacientes moribundos e de seus familiares, pois ajuda a reduzir a tanatofobia44 . Porém, na disciplina está prática ocorre somente uma vez, como já citado.Um estudo do Reino Unido feito com estudantes do último ano de medicina concluiu que o uso de role-play com dramatização, onde um estudante atua como o médico e o outro como o paciente ou familiar, durante 7 semanas, pode aumentar a confiança do acadêmico quando precisam notificar más notícias para o paciente como par os familiares45 .Foi observado, então, a existência de uma carência no preparo prático nessas disciplinas que discutem a morte e o morrer na universidade do presente estudo. De acordo com Wilson e Ayers 46 as oportunidades limitadas para intervenções médicas para os alunos e o extenso período como meros observadores podem levar a ansiedades sobre seu papel e menos conforto com a prática em pacientes para seus benefícios de seu aprendizado.…”
unclassified
“…article on the ability of role-play sessions to improve medical students' confidence in end-of-life consultations. 1 As final year medical students, we wish to draw upon our learning experience of death and dying and provide suggestions to enhance the current teaching.…”
Section: Improving Student Learning Of 'Unexpected Death'mentioning
confidence: 99%